A method of physically bonding a hydrogel to an elastomer, a hydrogel stretch sensor
Patent Information
- Application Number
- CN202311011152.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-11
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-08-11
AI Technical Summary
[0005]鉴于上述现有技术的不足,本发明的目的在于提供一种水凝胶与弹性体的物理粘接方法、水凝胶拉伸传感器,旨在解决水凝胶无法与粘合剂亲和形成稳固的界面,导致多层材料之间较低的界面强度的问题
[0021] Beneficial Effects: This invention discloses a physical bonding method for hydrogel and elastomer, and a hydrogel tensile sensor. By introducing a porous polymer film between the hydrogel and elastomer, a strong physical interlocking bond is achieved between the hydrogel and elastomer. The preparation method is simple and efficient, and the bonding strength is high, effectively preventing debonding during device deformation. It has strong applicability and is easy to promote and apply. The method provided by this invention can improve the interfacial peel toughness by tens of times, with a maximum 90-degree peel strength of 1269.70 N/m. The hydrogel tensile sensor prepared by this method can prevent debonding between the sensing layer and the substrate layer during deformation, and the physical interlocking is stable and reliable, ensuring normal operation of the device and improving its stability. This is of great significance to the development of flexible devices.
Smart Images

Figure CN117024816B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of flexible material preparation technology, and in particular to a physical bonding method for hydrogels and elastomers, and a hydrogel tensile sensor. Background Technology
[0002] In recent years, with the widespread attention and research on flexible materials and devices from researchers, scholars, and industries worldwide, flexible sensors have gradually become a research hotspot. Among them, novel flexible sensors composed of hydrogels and other soft materials are gradually attracting researchers' attention due to their excellent electrical and mechanical properties. It is worth noting that hydrogel sensors, due to their excellent compliance, stretchability, and biocompatibility, can adapt to the contours of object surfaces and withstand large tensile strains, showing great potential in wearable electronics, health monitoring, soft robotics, and other fields.
[0003] The normal operation of hydrogel sensors usually requires stable bonding with other elastomer materials to ensure the stability and accuracy of the sensor. However, due to the abundance of water molecules on its surface, hydrogels cannot form a stable interface with many adhesives, resulting in low interfacial strength between multilayer materials, which affects the performance of hydrogel sensors.
[0004] Currently, most bonding methods for hydrogels and elastomers rely on chemical bonding principles, such as surface modification and the introduction of covalent bonds. While these chemical bonding methods can achieve strong and tough bonds between hydrogels and elastomers to a certain extent, they struggle to maintain good stability under high-load operating conditions. Furthermore, the inherent properties of specific hydrogels can be interfered with by the chemically treated interface, thus affecting the sensor's performance. Therefore, existing technologies require further improvement and development. Researching methods to form a robust interface between hydrogels and elastomers without affecting the hydrogel's inherent properties, and thus realizing stretchable hydrogel devices with high interfacial strength, is of great significance. Summary of the Invention
[0005] In view of the shortcomings of the prior art, the purpose of this invention is to provide a physical bonding method for hydrogels and elastomers and a hydrogel tensile sensor, which aims to solve the problem that hydrogels cannot form a stable interface with adhesives, resulting in low interface strength between multilayer materials.
[0006] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows:
[0007] A method for physical bonding of a hydrogel and an elastomer, comprising the steps of:
[0008] The first polymer is dissolved in an organic solvent to obtain a polymer solution;
[0009] Sacrificial particles are added to the polymer solution and stirred to obtain a porous polymer mixture;
[0010] The porous polymer mixture is coated on the surface of an elastomer, and some sacrificial particles and all organic solvents are removed by a sacrificial template method to form a porous polymer film on the surface of the elastomer, thereby obtaining a porous elastomer composite material.
[0011] The hydrogel sol is coated onto the surface of the porous polymer film of the porous elastomer composite material and cross-linked to achieve physical bonding between the hydrogel and the elastomer.
[0012] The physical bonding method between the hydrogel and the elastomer, wherein the first polymer is selected from one or more of thermoplastic polyurethane, polyurethane, ethylene propylene diene monomer (EPDM), ethylene propylene diene monomer (EPDM), nitrile rubber, polyethylene, polypropylene, poly(1-butene), styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, styrene-ethylene-butene-styrene block copolymer, styrene-ethylene-propylene-styrene block copolymer, and polyethylene terephthalate; the organic solvent is selected from one or two of dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dimethyl isosorbide, dimethylpropenylurea, and hexamethylphosphoric triamine; and the polymer solution has a mass percentage of 20% to 40%.
[0013] The physical bonding method for the hydrogel and elastomer, wherein the mass ratio of the polymer solution to the sacrificial particles is 1:(2-6).
[0014] The physical bonding method between the hydrogel and the elastomer, wherein the sacrificial particles are selected from one or both of sodium chloride particles and fine sugar particles; the particle size of the sacrificial particles is 20-60 μm.
[0015] The physical bonding method between the hydrogel and the elastomer, wherein the coating thickness of the porous polymer mixture on the surface of the elastomer is 200-800 μm.
[0016] The physical bonding method between the hydrogel and the elastomer, wherein the hydrogel sol comprises a second polymer and water; the second polymer is selected from one or more of polyvinyl alcohol, polyacrylamide, polyoxyethylene, polyacrylic acid, sodium polyacrylate, acrylate, collagen, gelatin, hyaluronic acid, and chitosan.
[0017] The physical bonding method between the hydrogel and the elastomer, wherein the stirring is vacuum degassing stirring, and the vacuum degassing stirring time is 5 to 10 minutes.
[0018] The physical bonding method between the hydrogel and the elastomer, wherein the crosslinking treatment is selected from one of crystallization crosslinking treatment, ionic crosslinking treatment, and hydrogen bond crosslinking treatment; the temperature of the crosslinking treatment is -15℃ to -30℃, and the time of the crosslinking treatment is 10 to 15 hours.
[0019] A hydrogel stretch sensor includes a substrate layer, a connecting layer, a sensing layer, and an encapsulation layer arranged sequentially; wherein the sensing layer and the substrate layer are bonded together via the connecting layer using the method described above in this invention.
[0020] The hydrogel stretch sensor is wherein the encapsulation layer and the substrate layer are both polydimethylsiloxane elastomers, the sensing layer is a polyvinyl alcohol hydrogel, and the connecting layer is a porous thermoplastic polyurethane elastomer film.
[0021] Beneficial Effects: This invention discloses a physical bonding method for hydrogel and elastomer, and a hydrogel tensile sensor. By introducing a porous polymer film between the hydrogel and elastomer, a strong physical interlocking bond is achieved between the hydrogel and elastomer. The preparation method is simple and efficient, and the bonding strength is high, effectively preventing debonding during device deformation. It has strong applicability and is easy to promote and apply. The method provided by this invention can improve the interfacial peel toughness by tens of times, with a maximum 90-degree peel strength of 1269.70 N / m. The hydrogel tensile sensor prepared by this method can prevent debonding between the sensing layer and the substrate layer during deformation, and the physical interlocking is stable and reliable, ensuring normal operation of the device and improving its stability. This is of great significance to the development of flexible devices. Attached Figure Description
[0022] Figure 1 This is a flowchart of a preferred embodiment of a physical bonding method for hydrogels and elastomers provided by the present invention.
[0023] Figure 2 This is a schematic diagram illustrating the implementation principle of the physical bonding method between hydrogel and elastomer described in this invention.
[0024] Figure 3 This is a cross-sectional view of the interface of the hydrogel and elastomer composite material provided in Example 1.
[0025] Figure 4 The interfacial bond strength-displacement curve of the hydrogel and elastomer physical composite material provided in Example 1 is shown in the 90-degree peel test.
[0026] Figure 5 The interfacial bond strength-displacement curve of the hydrogel and elastomer physical composite material provided in Example 2 is shown in the 90-degree peel test.
[0027] Figure 6 The interfacial bond strength-displacement curve of the hydrogel and elastomer physical composite material provided in Example 3 is shown in the 90-degree peel test.
[0028] Figure 7 The interfacial bond strength-displacement curve of the hydrogel and elastomer physical composite material provided in Example 4 is shown in the 90-degree peel test. Detailed Implementation
[0029] This invention provides a method for physical bonding of hydrogel and elastomer, and a hydrogel tensile sensor. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the invention is further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.
[0030] Those skilled in the art will understand that, unless specifically stated otherwise, the singular forms “a,” “an,” “the,” and “the” used herein may also include the plural forms. It should be further understood that the term “comprising” as used in this specification means the presence of the stated features, integers, steps, operations, elements, and / or components, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components, and / or groups thereof.
[0031] It will be understood by those skilled in the art that, unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. It should also be understood that terms such as those defined in general dictionaries should be understood to have the same meaning as in the context of the prior art, and should not be interpreted in an idealized or overly formal sense unless specifically defined as herein.
[0032] The invention will be further explained below with reference to the accompanying drawings and the description of the embodiments.
[0033] The proper functioning of hydrogel sensors typically requires stable bonding with other elastomer materials to ensure sensor stability and accuracy. However, due to the abundance of water molecules on their surface, hydrogels cannot form robust interfaces with many adhesives, resulting in low interfacial strength between multilayer materials and affecting the performance of hydrogel sensors. Therefore, developing a method to achieve strong and tough bonding between hydrogels and elastomers is of great significance for the development and application of hydrogels and hydrogel sensors.
[0034] Based on this, the present invention provides a physical bonding method for hydrogels and elastomers, see [link to relevant documentation]. Figure 1 and Figure 2 It includes the following steps:
[0035] S10. Dissolve the first polymer in an organic solvent to obtain a polymer solution;
[0036] S20. Add the sacrificial particles to the polymer solution and stir to obtain a porous polymer mixture;
[0037] S30. The porous polymer mixture is coated on the surface of the elastomer, and some of the sacrificial particles and all the organic solvents are removed by the sacrificial template method to form a porous polymer film on the surface of the elastomer, thereby obtaining a porous elastomer composite material.
[0038] S40. The hydrogel sol is coated onto the surface of the porous polymer film of the porous elastomer composite material and cross-linked to achieve physical bonding between the hydrogel and the elastomer.
[0039] Specifically, this invention achieves a strong physical interlocking bond between the hydrogel and the elastomer by introducing a porous polymer film between them. The preparation method is simple and efficient, and the bonding strength is high, effectively preventing debonding during device deformation. It has strong applicability and is easy to promote and apply. The method provided by this invention can improve the interfacial peel toughness by tens of times, with a maximum 90-degree peel strength of 1269.70 N / m. The hydrogel tensile sensor prepared by this method can avoid debonding between the sensing layer and the substrate layer during deformation. Moreover, the physical interlocking is stable and reliable, ensuring the normal operation of the device and improving its stability, which is of great significance to the development of flexible devices.
[0040] In some embodiments, the first polymer is selected from one or more of thermoplastic polyurethane, polyurethane, ethylene propylene diene monomer (EPDM), ethylene propylene diene monomer (EPDM), nitrile rubber, polyethylene, polypropylene, poly(1-butene), styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, styrene-ethylene-butene-styrene block copolymer, styrene-ethylene-propylene-styrene block copolymer, and polyethylene terephthalate; the organic solvent is selected from one or two of dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dimethyl isosorbide, dimethylpropenylurea, and hexamethylphosphoric triamine; the polymer solution has a mass percentage of 20% to 40%, preferably 25% to 33%. Within this mass percentage range of the polymer solution, a strong bond can be achieved between the hydrogel and the elastomer substrate. If the mass percentage of the polymer solution is too low, the modulus of the prepared porous polymer film will be too low, making it unable to form a strong physical bond interface with the hydrogel and the elastomer substrate, ultimately resulting in a low interfacial bonding energy. If the mass percentage of the polymer solution is too high, the fluidity of the solution will be poor, and the thickness of the prepared porous polymer film will increase, thereby weakening the energy dissipation effect during interfacial peeling, ultimately resulting in a low interfacial bonding energy.
[0041] In some embodiments, the mass ratio of the polymer solution to the sacrificial particles is 1:(2-6). Within this range of polymer solution to sacrificial particle mass ratio, porous polymer films with suitable and uniform pore size distribution can be prepared. If the mass ratio of polymer solution to sacrificial particles is too small, the porous polymer film will have uneven pore size, low modulus, and loose structure, making it unable to firmly bond with the elastomer substrate, ultimately resulting in low interfacial adhesion energy. If the mass ratio of polymer solution to sacrificial particles is too large, a sufficient number of pores cannot be formed, the contact area between the hydrogel and the porous polymer film is too small, and a robust physical bonding interface cannot be formed, ultimately resulting in low interfacial adhesion energy.
[0042] In some embodiments, the sacrificial particles are solid particles that are insoluble in organic solvents but soluble in water, so that some of the sacrificial particles can be detached during the subsequent use of the sacrificial template method to form a porous structure; specifically, the sacrificial particles are selected from one or both of sodium chloride particles and fine sugar particles; the particle size of the sacrificial particles is 20-60 μm, preferably 30-40 μm.
[0043] In some embodiments, the elastomer is selected from one or more of polydimethylsiloxane, hydrogenated styrene-butadiene block copolymer, and styrene-based thermoplastic elastomers.
[0044] In some embodiments, the porous polymer mixture is coated on the surface of the elastomer with a thickness of 200–800 μm. The porous polymer film is characterized by uniformly distributed pores with consistent pore size, the pore size being related to the particle size of the sacrificial particles, and the film thickness being related to the coating thickness. Preferably, the coating thickness is 400–600 μm.
[0045] In some embodiments, the sacrificial template method specifically involves placing the elastomer coated with the porous polymer solution into water containing some sacrificial particles and all organic solvents.
[0046] In some embodiments, the hydrogel sol comprises a second polymer and water; the second polymer includes, but is not limited to, one or more of polyvinyl alcohol, polyacrylamide, polyoxyethylene, polyacrylic acid, sodium polyacrylate, acrylate, collagen, gelatin, hyaluronic acid, and chitosan, and may also be other copolymers with abundant hydrophilic groups; the hydrogel sol is not limited to these, and may be a hydrogel sol well known to those skilled in the art.
[0047] In some embodiments, the stirring method is not limited to this and can be any stirring method well known to those skilled in the art, as long as the sacrificial particles can be uniformly dispersed in the polymer solution and no bubbles are present; preferably, the stirring is vacuum degassing stirring, and the vacuum degassing stirring time is 5 to 10 minutes.
[0048] In some embodiments, the crosslinking treatment is selected from one of crystallization crosslinking treatment, ionic crosslinking treatment, and hydrogen bond crosslinking treatment, so that the hydrogel sol crosslinks into a gel, preferably crystallization crosslinking treatment; the temperature of the crosslinking treatment is -15℃ to -30℃, preferably -20℃, and the time of the crosslinking treatment is 10 to 15 hours, preferably 12 hours.
[0049] A hydrogel stretch sensor includes a substrate layer, a connecting layer, a sensing layer, and an encapsulation layer arranged sequentially; wherein the sensing layer and the substrate layer are bonded together via the connecting layer using the method described above in this invention.
[0050] In some embodiments, the encapsulation layer and the substrate layer are both polydimethylsiloxane elastomers, the sensing layer is a polyvinyl alcohol hydrogel, and the connecting layer is a porous thermoplastic polyurethane elastomer film.
[0051] By applying the bonding method of the present invention to hydrogel tensile sensors, the stability and accuracy of the hydrogel tensile sensors can be improved.
[0052] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of the present invention, not all embodiments, and are intended only to illustrate the present invention and not to limit it. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0053] Example 1
[0054] This embodiment provides a physical bonding method for polyvinyl alcohol hydrogel and polydimethylsiloxane elastomer, the physical bonding method specifically including the following steps:
[0055] S10. Add thermoplastic polyurethane elastomer particles to dimethylformamide organic solvent to prepare a thermoplastic polyurethane elastomer solution with a mass fraction of 25%.
[0056] S20. Add sodium chloride with a particle size of 30 micrometers as sacrificial particles to the thermoplastic polyurethane elastomer solution at a mass ratio of 1:4, and vacuum degas and stir for 5 minutes until it is fully and uniformly dispersed to obtain a porous polymer mixture.
[0057] S30. The porous polymer mixture is uniformly coated on the surface of the polydimethylsiloxane elastomer with a thickness of 500 micrometers. The polydimethylsiloxane elastomer coated with the porous polymer solution is then placed in a beaker containing water and soaked at room temperature for 2 hours. After soaking, the sodium chloride particles and dimethylformamide organic solvent are removed by the sacrificial template method. The elastomer is then dried at 80°C for 30 minutes to remove excess moisture, resulting in a porous polymer film that is tightly bonded to the polydimethylsiloxane elastomer.
[0058] S40. Prepare a 10% polyvinyl alcohol sol by mass, then add 30% glycerol by mass to the polyvinyl alcohol sol, heat at 80°C for 2 hours and stir evenly; after cooling, coat it evenly on the porous polymer film, let it stand under vacuum for 5 minutes to remove air bubbles and fill the pores of the porous polymer film, then put it into a sealed box and seal it, freeze at -20°C for 12 hours, and then thaw at room temperature for 1 hour to complete the bonding of polyvinyl alcohol hydrogel and polydimethylsiloxane elastomer.
[0059] Figure 3 This is a cross-sectional view of the interface of the hydrogel and elastomer composite material provided in Example 1.
[0060] Figure 4 The interfacial adhesion energy-displacement curve of the hydrogel and elastomer physical composite material provided in Example 1 is obtained from the 90-degree peel test. Figure 4As can be seen, a 100-micron thick polycarbonate film was bonded to the back of the hydrogel using cyanoacrylate adhesive as a rigid backing for testing. The adhesion strength between the polyvinyl alcohol hydrogel and the polydimethylsiloxane elastomer was tested using a 90-degree peel tester at a speed of 1 mm / s. The highest 90-degree peel strength was 660.35 N / m.
[0061] Example 2
[0062] This embodiment provides a physical bonding method for polyvinyl alcohol hydrogel and polydimethylsiloxane elastomer. The difference between this physical bonding method and that of Embodiment 1 is that the mass fraction of glycerol added in step S40 is 10%, while the other preparation steps are the same as in Embodiment 1.
[0063] Figure 5 The interfacial adhesion energy-displacement curve of the hydrogel and elastomer physical composite material provided in Example 2 is obtained from the 90-degree peel test. Figure 5 As can be seen, a 100-micron thick polycarbonate film was bonded to the back of the hydrogel using cyanoacrylate adhesive as a rigid backing for testing. The adhesion strength between the polyvinyl alcohol hydrogel and the polydimethylsiloxane elastomer was tested using a 90-degree peel tester at a speed of 1 mm / s. The highest 90-degree peel strength was 971.15 N / m.
[0064] Example 3
[0065] This embodiment provides a physical bonding method for polyvinyl alcohol hydrogel and polydimethylsiloxane elastomer. The difference between this physical bonding method and that of Embodiment 1 is that the mass fraction of glycerol added in step S40 is 20%, while the other preparation steps are the same as in Embodiment 1.
[0066] Figure 6 The interfacial adhesion energy-displacement curve of the hydrogel and elastomer physical composite material provided in Example 3 is obtained from the 90-degree peel test. Figure 6 As can be seen, a 100-micron thick polycarbonate film was bonded to the back of the hydrogel using cyanoacrylate adhesive as a rigid backing for testing. The adhesion strength between the polyvinyl alcohol hydrogel and the polydimethylsiloxane elastomer was tested using a 90-degree peel tester at a speed of 1 mm / s. The highest 90-degree peel strength was 1269.70 N / m.
[0067] Example 4
[0068] This embodiment provides a physical bonding method for polyacrylamide hydrogel and polydimethylsiloxane elastomer, the physical bonding method specifically including the following steps:
[0069] S10. Add thermoplastic polyurethane elastomer particles to dimethylformamide organic solvent to prepare a thermoplastic polyurethane elastomer solution with a mass fraction of 25%.
[0070] S20. Add sodium chloride with a particle size of 30 micrometers as sacrificial particles to the thermoplastic polyurethane elastomer solution at a mass ratio of 1:4, and vacuum degas and stir for 5 minutes until it is fully and uniformly dispersed to obtain a porous polymer mixture.
[0071] S30. The porous polymer mixture is uniformly coated on the surface of the polydimethylsiloxane elastomer with a thickness of 500 micrometers. The polydimethylsiloxane elastomer coated with the porous polymer solution is then placed in a beaker containing water and soaked at room temperature for 2 hours. After soaking, the sodium chloride particles and dimethylformamide organic solvent are removed by the sacrificial template method. The elastomer is then dried at 80°C for 30 minutes to remove excess moisture, resulting in a porous polymer film that is tightly bonded to the polydimethylsiloxane elastomer.
[0072] S40. Prepare a 10% polyacrylamide sol by mass, then add 30% glycerol by mass to the polyacrylamide sol, heat at 80°C for 2 hours and stir until uniform; after cooling, uniformly coat it onto the porous polymer film, let it stand under vacuum for 5 minutes to remove air bubbles and fill the pores of the porous polymer film, then put it into a sealed box and seal it, freeze at -20°C for 12 hours, and then thaw at room temperature for 1 hour to complete the bonding of polyacrylamide hydrogel and polydimethylsiloxane elastomer.
[0073] Figure 7 The interfacial adhesion energy-displacement curve of the hydrogel and elastomer physical composite material provided in Example 4 is obtained from the 90-degree peel test. Figure 7 As can be seen, a 100-micron thick polycarbonate film was bonded to the back of the hydrogel using cyanoacrylate adhesive as a rigid backing for testing. The adhesion strength between the polyacrylamide hydrogel and the polydimethylsiloxane elastomer was tested using a 90-degree peel tester at a speed of 1 mm / s. The highest 90-degree peel strength was 1227.25 N / m.
[0074] In summary, this invention discloses a method for physical bonding of hydrogel and elastomer, and a hydrogel tensile sensor. The method includes the following steps: dissolving a first polymer in an organic solvent to obtain a polymer solution; adding sacrificial particles to the polymer solution and stirring to obtain a porous polymer mixture; coating the porous polymer mixture onto the surface of an elastomer, removing some of the sacrificial particles and all of the organic solvent using a sacrificial template method to form a porous polymer film on the surface of the elastomer, obtaining a porous elastomer composite material; and coating a hydrogel sol onto the surface of the porous polymer film of the porous elastomer composite material for crosslinking treatment to achieve physical bonding between the hydrogel and the elastomer. This invention achieves a strong physical interlocking bond between the hydrogel and the elastomer by introducing a porous polymer film between them. The preparation method is simple and efficient, and the bonding strength is high, effectively preventing debonding during device deformation. It has strong applicability and is easy to promote and apply. The method provided by this invention can improve the interfacial peel toughness by tens of times, with a maximum peel strength of 1269.70 N / m at 90 degrees. The hydrogel tensile sensor prepared by this method can avoid debonding between the sensing layer and the substrate layer during deformation. Moreover, the physical interlocking is stable and reliable, ensuring the normal operation of the device and improving its stability, which is of great significance to the development of flexible devices.
[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or make equivalent substitutions for some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for physical bonding of a hydrogel and an elastomer, characterized in that, Including the following steps: The first polymer is dissolved in an organic solvent to obtain a polymer solution; Sacrificial particles are added to the polymer solution and stirred to obtain a porous polymer mixture; The porous polymer mixture is coated on the surface of an elastomer, and some sacrificial particles and all organic solvents are removed by a sacrificial template method to form a porous polymer film on the surface of the elastomer, thereby obtaining a porous elastomer composite material. The hydrogel sol is coated onto the surface of the porous polymer film of the porous elastomer composite material and cross-linked to achieve physical bonding between the hydrogel and the elastomer. The polymer solution has a mass percentage of 20% to 40%. The mass ratio of the polymer solution to the sacrificial particles is 1:(2~6). The sacrificial particles are selected from one or both of sodium chloride particles and fine sugar particles; the particle size of the sacrificial particles is 30~40μm; The porous polymer mixture is coated on the surface of the elastomer with a thickness of 200~800μm; The crosslinking treatment is a crystallization crosslinking treatment; the temperature of the crosslinking treatment is -15℃ to -30℃, and the time of the crosslinking treatment is 10 to 15 hours; the first polymer is thermoplastic polyurethane.
2. The physical bonding method between hydrogel and elastomer according to claim 1, characterized in that, The organic solvent is selected from one or two of dimethylformamide, dimethylacetamide, dimethyl sulfoxide, dimethyl isosorbide, dimethylpropenylurea, and hexamethylphosphoric triamine.
3. The physical bonding method for hydrogel and elastomer according to claim 1, characterized in that, The hydrogel sol comprises a second polymer and water; the second polymer is selected from one or more of polyvinyl alcohol, polyacrylamide, polyoxyethylene, polyacrylic acid, sodium polyacrylate, collagen, gelatin, hyaluronic acid, and chitosan.
4. The physical bonding method between hydrogel and elastomer according to claim 1, characterized in that, The stirring is vacuum degassing stirring, and the vacuum degassing stirring time is 5~10 minutes.
5. A hydrogel stretch sensor, characterized in that, It includes a substrate layer, a connecting layer, a sensing layer and an encapsulation layer arranged sequentially; wherein the sensing layer and the substrate layer are bonded together by means of the connecting layer as described in any one of claims 1 to 4.
6. The hydrogel stretch sensor according to claim 5, characterized in that, Both the encapsulation layer and the substrate layer are polydimethylsiloxane elastomers, the sensing layer is a polyvinyl alcohol hydrogel, and the connecting layer is a porous thermoplastic polyurethane elastomer film.
Citation Information
Patent Citations
Porous conductive paste for preparing flexible piezoresistive sensor and preparation method and application thereof
CN109785995A
Stretchable humidity sensor with thin film structure and manufacturing method and application thereof
CN113237924A
Method of bonding polymer gel
JP2011162648A